The Influence of EWOM Dimensions, Purchase Intention on Buying Behavior in Women's Clothing Products in Java Island - Sherly Sherly; Endang Ruswanti (Green Publisher Indonesia, 2024)
This research aims to analyze the influence of information quality, information quantity, information credibility, information task-fit, information needs and attitudes towards information on purchasing behavior for women's clothing products directly or through the mediation of purchase intentions. This research was applied to social media users such as Tiktok, Instagram and Facebook. The sample was determined using a purposive sampling technique so that 140 respondents were obtained. Research data was collected using a research questionnaire and carried out statistical analysis using partial least squares. The research results show that information quality, information quantity, information credibility, information task-fit, information needs and attitudes towards information partially have a positive and significant effect on purchase intentions, then purchase intentions have a positive and significant effect on purchasing behavior for women's clothing products. The purchase intention variable plays its role well as a mediating variable